From Leadership to Legitimacy Crisis: Lexicon of Peace in Media Discourse on Sheikh Hasina’s Resignation - Hasan Shaikh (Darul Yasin Al Sys, 2026)
Political transitions are not only institutional events but also discursive processes through which leadership, legitimacy, resistance, and peace are publicly reconstructed. The resignation of Sheikh Hasina during Bangladesh’s 2024 protests provides a significant case for examining how media discourse negotiates political authority and social transformation. This study aims to analyze media representations of Sheikh Hasina’s resignation and to investigate how discourse, ideology, and peacebuilding narratives are constructed around this political transition. Employing Fairclough’s three-dimensional model of critical discourse analysis, the study examines a strategically selected corpus of 22 national and international news articles. The findings reveal that Hasina’s resignation was framed less as a political retreat than as a discursive reckoning in which her leadership legacy was reconstructed retrospectively, while student slogans challenged established power through irony, solidarity, and collective identification. Through selective lexical choices, shifts in agency, competing ideological positions, and editorial framing, media narratives discursively represented both the erosion of political legitimacy and the emergence of popular agency. Hasina’s silence at the moment of departure constituted a significant discursive absence subsequently filled by military statements, protest slogans, and journalistic interpretation. Despite her historical position as the longest-serving female head of government, gendered perspectives were largely absent from the analyzed coverage, suggesting a symbolic marginalization of gender within narratives of political failure. The study further demonstrates how peace was reframed from an imposed political order toward a discourse of collective renewal shaped by protest, memory, and popular participation. These findings contribute to critical discourse studies by demonstrating how media language participates in reconstructing legitimacy during political crises and transitions. The study also highlights the importance of media literacy in post-conflict contexts where competing interpretations of truth, justice, leadership, and collective memory continue to be negotiated.